Architecture of the Known and Unknown: Defining and Inhabiting Peripheries (EAAE Joint Publishings, 2026)
he establishment of an edge, of limits, or a periphery, is fundamental to architecture. It is thefoundation of the difference between the known and unknown, inside and outside, the zone of significant energy transfers, and the making of ‘place.’ The term ‘placemaking” may be a cliché, but there is an essential truth in the concept that makes it worth re-evaluation and definition in the context of current discourse. With that in mind, this paper will investigate how architectural peripheries are established, how they operate to mediate inside from outside, the transfer of information, and how humans then fully establish their possession of a place in the world.  This paper investigates (1) how architectural peripheries are established and their intentions; (2) the context of the familiar: how the known prepares us for the unknown; (3) how edges may not simply be a recognition of differences, but the invention of difference; (4) how difference between inside (known) and outside (unknown) is more than a conclusive barrier, but a mediation of degrees of enclosure; (5) how human activities occasion familiarity or possession of a place; (6) the notion that recently we have experienced an inversion of the inside as the place of contentment and outside as the location of unease; and (7) preliminary conclusions, mainly, the case for openness and vulnerability as modeled by a range of edges and the possibility of architecture as a model for the productive entanglement of known and unknown.Citing specific aspects of architecture and the natural world from diverse cultures in which the values of edges, information transfer, human interaction, and designed spaces are represented, this paper examines the nature of peripheries, the inhabitation of edges, the making of degrees of enclosure, and the particularizing layers of space that intervene between inside and outside that create “difference.”